New precisely dated pyroclastic deposits from Pliocene-Pleistocene volcanic activity in the central parts of Southeastern Europe - Kata Molnár; Pierre Lahitte; Zsolt Benkó; Јános Szepesi; Maxim Portnyagin; Daniel Frick; Samuele Agostini; Sebastien Nomade; Maria Giuditta Fellin; Colin Maden; Ivan Boev; Blažo Boev; et al. (Journal of Volcanology and Geothermal Research, 2026)

Unveiling the hidden source of major historical earthquakes: A multi-scale, trans-disciplinary approach to the 1456 and 1688 Sannio earthquakes (Mw 7.0, southern Italian Apennines) - Vincenzo Amato; Sabatino Ciarcia; Paolo Galli; Domenico Cicchella; Antonio Galderisi; Lorenzo Monaco; Giada Fernandez; Roberto Isaia; Sebastien Nomade; Alison Pereira; Biagio Giaccio (Quaternary Science Reviews, 2025)

Geological, paleoenvironmental, and depositional dynamics at the Middle Pleistocene Palaeoloxodon antiquus-bearing site of Campo della Spina, Central Italy - Paul P.A. Mazza; Fabrizio Marra; Giovanni Maria Di Buduo; Luca Bellucci; Mirko Bonechi; Ezra Goemans; Cosimo Bonechi; Luca Costantini; Sebastien Nomade; Danilo M. Palladino; Alison Pereira; Andrea Savorelli (Quaternary International, 2024)

Magma storage conditions beneath a peralkaline caldera in the Main Ethiopian Rift - David J. Colby; David M. Pyle; Karen Fontijn; Tamsin A. Mather; Sebastien Nomade; Abate A. Melaku; Million A. Mengesha; Gezahegn Yirgu (Journal of Volcanology and Geothermal Research, 2024)

Multidisciplinary study of the Lower Palaeolithic site of Cimitero di Atella (Basilicata), Italy - Roxane Rocca; Paolo Giannandrea; Alison Pereira; Jean-Jacques Bahain; Francesco Boschin; Amélie Da Costa; Federico Di Rita; François Fouriaux; Alessio Iannucci; Lucie Germond; Dario Gioia; Donatella Magri; et al. (Quaternary International, 2023)

Unravelling the pre-eruptive conditions of the rhyolitic Šumovit Greben lava dome from clinopyroxene-dominant glomeroporphyritic clots - Kata Molnár; Pierre Lahitte; Boglárka Döncző; Róbert Arató; János Szepesi; Zsolt Benkó; Sebastien Nomade; Jochen Gätjen; Stéphane Dibacto; Marjan Temovski (Contributions to Mineralogy and Petrology, 2023)
Detailed analyses of mineral composition and whole-rock geochemical data helped to unravel the volcanic plumbing system beneath the rhyolitic Šumovit Greben lava dome, the westernmost member of the Kožuf-Voras volcanic system (N. Macedonia). It is characterized by high SiO 2 content (> 70 wt%) coupled with low MgO (< 1 wt%) and Sr (< 500 ppm) suggesting fractionation of clinopyroxene and plagioclase at depth forming a crystal mush and a crystal-poor rhyolitic lens by fractional crystallization and melt extraction on top of it. The crystal mush is composed of mainly clinopyroxene, biotite and plagioclase, whereas sanidine and plagioclase are the most abundant phenocrysts of the rhyolitic lens. The main dome forming event occurred at ca. 2.9 Ma, which sampled the crystal-poor rhyolitic lens. After a short quiescence time, an explosive eruption occurred depositing a massive lapilli tuff layer northwest of the lava dome, and an extrusion of a small-volume lava flow on the northern side of the lava dome at ca. 2.8 Ma. This latter sampled also the crystal mush, as it contains abundant glomeroporphyritic clots of clinopyroxene ± plagioclase ± biotite. The clinopyroxene phenocrysts are chemically homogeneous, their crystallization temperature is ca. 900 °C representing the crystal mush, whereas the plagioclase and the sanidine crystallized at a lower temperature (ca. 790 °C) representing the rhyolitic lens. Noble gas isotopic composition of the clinopyroxene indicate no mantle-derived fluids (< 0.5%) having an R/R a of ca. 0.04 R a . The rejuvenation of the system probably occurred due to implementation of mafic magma at depth leading to a heat transfer and partial melting of the cumulate. This led to crystallization of Ba-rich rims of the sanidine and An- and Sr-rich rims of the plagioclase. The crystal mush zone beneath Šumovit Greben might be connected to the nearby, more mafic volcanic centers, and the eruption of Šumovit Greben could have been the start of the last cycle in the lifetime of the Kožuf-Voras volcanic system.

Hydrological variability over the Apennines during the Early Last Glacial precession minimum, as revealed by a stable isotope record from Sulmona basin, Central Italy - ELEONORA REGATTIERI; BIAGIO GIACCIO; GIOVANNI ZANCHETTA; RUSSELL N. DRYSDALE; PAOLO GALLI; SEBASTIEN NOMADE; EDOARDO PERONACE; SABINE WULF (Journal of Quaternary Science, 2015)
A multi‐proxy record was acquired from a Late Pleistocene lacustrine succession in the Sulmona basin, central Italy. Previous and new tephrostratigraphic analyses of six volcanic ash layers constrain the investigated interval to between 92.3 and 115.0 ka. The δ 18 O composition is interpreted as a proxy for precipitation amount in the high‐altitude catchment of the karst recharge system. The oxygen record shows millennial variability that is consistent with Greenland Interstadials GI25–23 and North Atlantic cold events C24–C22, indicating a strong Mediterranean–North Atlantic climate teleconnection. However, while no appreciable isotopic difference between the three interstadials is revealed by the Greenland record, the Sulmona section reveals a wetter climate during GI24 compared with GI23 and GI25. Comparison of our record with speleothem and pollen data from central and southern Italy suggests higher seasonality of the precipitation (wet winter–dry summer) for GI24, which matches a precession minimum. The wettest period recorded at Sulmona is also coincident with the deposition of Sapropel S4 in the Tyrrhenian Sea, suggesting a teleconnection between a higher seasonality in the western Mediterranean and strengthening of the boreal monsoon system.

A 560–440 ka tephra record from the Mercure Basin, southern Italy: volcanological and tephrostratigraphic implications - BIAGIO GIACCIO; PAOLO GALLI; EDOARDO PERONACE; ILENIA ARIENZO; SEBASTIEN NOMADE; GIAN PAOLO CAVINATO; MARCO MANCINI; PAOLO MESSINA; GIANLUCA SOTTILI (Journal of Quaternary Science, 2014)
Integrated electron microprobe analyses (EMPAs) on glass and Sr–Nd isotope analyses have been performed on 17 tephras from the Middle Pleistocene Mercure lacustrine succession, southern Apennines. Two 40 Ar/ 39 Ar ages and the recognition of four relevant tephras from Colli Albani, Sabatini and possibly Roccamonfina volcanoes allowed us to ascribe the investigated succession to the late Marine Isotope Stage (MIS) 15–12 interval (560–440 ka). The Sr–Nd isotopes and major element glass compositions allowed us to attribute 10 out of the other 13 tephras to a poorly known activity of the Roccamofina volcano, whereas two layers were tentatively attributed to previously unknown Middle Pleistocene activity of Ponza Island or Campanian volcanoes, and one to Salina Island. The tephrostratigraphic correlation of the Mercure tephras with the Acerno lacustrine pollen record (Campania) also allowed us to evaluate the climatostratigraphic position of the tephras within the framework of the MIS 15–12 climatic variability. These results were obtained by combining the Sr–Nd isotope ratio with EMPA and 40 Ar/ 39 Ar geochronological data. This confirms the notable consistency of this approach for studying the Mediterranean Middle Pleistocene tephrostratigraphy, which, despite its great potential for both volcanology and Quaternary studies, has been hitherto barely explored.

Revised Chronology of the Sulmona Lacustrine Succession, Central Italy - BIAGIO GIACCIO; FRANCESCA CASTORINA; SEBASTIEN NOMADE; GIANCARLO SCARDIA; MARIO VOLTAGGIO; LEONARDO SAGNOTTI (Journal of Quaternary Science, 2013)
We present new stratigraphic, palaeomagnetic, 87 Sr/ 86 Sr and 40 Ar/ 39 Ar data from a lacustrine succession of the Sulmona basin, central Italy, which, according to an early study, included six unconformity‐bounded lacustrine units (from SUL6, oldest, to SUL1, youngest) spanning the interval >600 to 2 ka. The results of the present study, on the one hand confirm some of the previous conclusions, but by contrast reveal that units SUL2 and SUL1, previously attributed to the Holocene, are actually equivalent to the older SUL6 and SUL5 units – here dated to ∼814–>530 ka and ∼530–